2001
DOI: 10.1515/hf.2001.071
|View full text |Cite
|
Sign up to set email alerts
|

Wood Surface Energy and Time Dependence of Wettability: A Comparison of Different Wood Surfaces Using an Acid-Base Approach

Abstract: a) microtomed surface prepared on a sledge microtome (5 samples/species) b) roughly sanded surface (P100) (5 samples/species) Holzforschung / Vol. 55 / 2001 / No. 4 SummaryUsing four different wood species, the wetting behaviour of sanded wood surfaces was compared with that of microtomed surfaces. Sanding caused lower contact angles and lower total surface free energies. Electron donor components were considered to be responsible for the observed changes according to the applied acid-base approach. The tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
(40 reference statements)
2
24
1
3
Order By: Relevance
“…For fresh wood, the critical surface free energy according to the Zisman method (Timmons and Zisman 1968) is systematically 30 to 40% lower than that calculated by the OWRK method (Owens and Wendt 1969). A similar occurrence was observed by Maldas and Kamdem (1998) and Gindl et al (2001a). However, for aged wood, the changes in surface free energy among the Zisman method (Timmons and Zisman 1968), OWRK method (Owens and Wendt 1969), and vOCG method (Van Oss et al 1988) were not evident (Fig.…”
Section: Surface Free Energy Componentssupporting
confidence: 74%
“…For fresh wood, the critical surface free energy according to the Zisman method (Timmons and Zisman 1968) is systematically 30 to 40% lower than that calculated by the OWRK method (Owens and Wendt 1969). A similar occurrence was observed by Maldas and Kamdem (1998) and Gindl et al (2001a). However, for aged wood, the changes in surface free energy among the Zisman method (Timmons and Zisman 1968), OWRK method (Owens and Wendt 1969), and vOCG method (Van Oss et al 1988) were not evident (Fig.…”
Section: Surface Free Energy Componentssupporting
confidence: 74%
“…Recently, as well as in the past, much research has been undertaken examining differences in wood surface free energy in relation to the properties of porosity and anisotropy. It was found that the species, surface roughness, pH value, and aging time all influenced surface free energy (Cao et al 2005, Gindl et al 2001b, Little et Qin et al (2014. "Wood wettability & machining," BioResources 9(2), 3088-3103.…”
Section: Introductionmentioning
confidence: 99%
“…The wettability of the wood surface is used to determine the weathering mechanism. SFE is a characteristic of wood that depends on species, pH value, surface roughness, and aging time (Gindl, Sinn, Reiterer, & Tschegg, 2001;Gindl & Tschegg, 2002;Little, McConnell, Irby, Shi, & Riggins, 2013). Gérardin, Petrič, Petrissans, Lambert, and Ehrhrardt (2007) have evaluated wood SFE after being treated with heat, and the wettability of the heat-treated wood was strongly affected, causing changes to its behaviour.…”
mentioning
confidence: 99%